The relationship between gender, age, mental ability, anxiety, mathematics self-efficacy and achievement in mathematics (2009)
This study examines the relationship between gender, age, general mental ability, anxiety, mathematics self-efficacy and achievement in mathematics among senior secondary school students in Oyo State, Nigeria. Using multiple regression (stepwise) statistical procedures on the data collected from 1,099 SS2 students, results reveal that mathematics self-efficacy, gender and anxiety have significant correlations with student's achievement in mathematics. Mathematics self-efficacy is the best predictor of mathematics achievement followed by gender and anxiety. The need for educational stakeholders and curriculum planners to design programmes that will enhance mathematics self-efficacy of students was discussed.